The Customer Isn't Always Right—Conservation and Animal Welfare Implications of the Increasing Demand for Wildlife Tourism - Moorhouse, Tom P.; Dahlsjö, Cecilia A. L.; Baker, Sandra E.; D'Cruze, Neil C.; Macdonald, David W. (PloS one, 2015)
Tourism accounts for 9% of global GDP and comprises 1.1 billion tourist arrivals per annum. Visits to wildlife tourist attractions (WTAs) may account for 20-40% of global tourism, but no studies have audited the diversity of WTAs and their impacts on the conservation status and welfare of subject animals. We scored these impacts for 24 types of WTA, visited by 3.6-6 million tourists per year, and compared our scores to tourists' feedback on TripAdvisor. Six WTA types (impacting 1,500-13,000 individual animals) had net positive conservation/welfare impacts, but 14 (120,000-340,000 individuals) had negative conservation impacts and 18 (230,000-550,000 individuals) had negative welfare impacts. Despite these figures only 7.8% of all tourist feedback on these WTAs was negative due to conservation/welfare concerns. We demonstrate that WTAs have substantial negative effects that are unrecognised by the majority of tourists, suggesting an urgent need for tourist education and regulation of WTAs worldwide.